Analisis Biaya Pekerjaan Timbunan Tanah Dengan Metode Photogrammetry - Andita Oktavia; Retna Kristiana (Journal of Applied Civil Engineering and Infrastructure Technology, 2026)
Recently, the construction industry has rapidly developed technology, particularly in infrastructure construction. One alternative is Free and Open Source Software (FOSS) Photogrammetry to factor in the cost of landfill work on the Padang – Sicincin toll road project. The photogrammetry method is a science and part of the art of obtaining mathematically precise measurements. The photogrammetry method can be an alternative solution for increasing cost effectiveness in projects with direct cost calculations. Surveyors conduct data measurement in the hoarding work for each layer of the Padang - Sicincin toll road project. Then, in the field, there was an inaccuracy in the x, y, z results when data was collected using a total station. According to the analysis results, the volume of the fill material deviated by 5.4%. The photogrammetry method indicated a difference of 26.95 m³ more than the manual method. The cost deviation from the previously calculated volume results was Rp2,234,719.26, making the photogrammetry method cheaper than the manual method.